Nature - Pets: Wild at Heart - Secretive Creatures. (PBS, 2015)
The second of a two-part series, Secretive Creatures looks into how our pets experience their world through hidden channels of communication revealed with ultra slow-motion, photography that makes smells visible, X-rays that reveal hidden powers, and ultraviolet light that brings out the best in birds..